The Anthropological Nature of the Crowd in the Context of Postmodernity - Babajanyan, Levon (Bulletin of Yerevan University E: Philosophy, Psychology, 2016)
The article considers the anthropological nature of the man of the crowd in the context of current sociocultural transformations. If the crowd of the era of modernity was determined as an emotional, aggressive, politically pretentious social organism, therefore in the era of postmodernity the crowd purchases sociocultural features like indifference, passivity, cynicism and so on. The shape of the current man of the crowd is determined by the sociocultural features of the era of postmodernity, like consumption, political indifference, hedonism, and cynicism.